Tourism, Empowerment and Sustainable Development: A New Framework for Analysis - Regina Scheyvens (MDPI AG, 2021)
For over twenty years, tourism researchers have examined how to determine whether destination communities are being empowered through tourism: there is much we can learn through analysis of that work. We outline and critique the most commonly used empowerment framework in this field as was first published by Scheyvens in 1999, which has four dimensions (psychological, social, economic and political) but which has been adapted and extended in a variety of ways. We also consider two other frameworks, and the application of a revised model in the South African context, before proposing that the Scheyvens framework would be strengthened through the addition of environmental and cultural dimensions. We draw theoretical inspiration from nested circle approaches to sustainable development to embed the dimensions of community empowerment within a series of ‘enabling factors’ that might support possibilities for community empowerment to occur, and, in turn, the empowerment dimensions and enabling factors are situated within a wider circle of the natural environment. We have structured this all into a new Empowerment and Sustainable Development Framework.